2017
DOI: 10.3389/fnmol.2017.00116
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Ectodomain of Neuroligin 1 Decreases Synaptic Activity by Activating Metabotropic Glutamate Receptor 2

Abstract: Synaptic cell adhesion molecules represent important targets for neuronal activity-dependent proteolysis. Postsynaptic neuroligins (NLs) form trans-synaptic complexes with presynaptic neurexins (NXs). Both NXs and NLs are cleaved from the cell surface by metalloproteases in an activity-dependent manner, releasing a soluble extracellular fragment and membrane-tethered C-terminal fragment. The cleavage of NL1 depresses synaptic transmission, but the mechanism by which this occurs is unknown. Metabotropic glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Neurexins and neuroligins are important transmembrane adhesion proteins in the regulation of synapse function. 11 , 43 46 The expressions of neuroligin1 and neuroligin2 in the central nervous system are restricted to excitatory and inhibitory synapses, respectively. 18 , 47 49 Neuroligin1 is enriched at the postsynaptic densities of excitatory synapses containing the scaffolding protein PSD-95.…”
Section: Discussionmentioning
confidence: 99%
“…Neurexins and neuroligins are important transmembrane adhesion proteins in the regulation of synapse function. 11 , 43 46 The expressions of neuroligin1 and neuroligin2 in the central nervous system are restricted to excitatory and inhibitory synapses, respectively. 18 , 47 49 Neuroligin1 is enriched at the postsynaptic densities of excitatory synapses containing the scaffolding protein PSD-95.…”
Section: Discussionmentioning
confidence: 99%
“…For example, proteolytic cleavage of Nlg-1 prevents its surface expression, leading to the destabilization of trans-synaptic Nrx–Nlg complexes [ 55 , 56 ]. Furthermore, the extracellular fragments of Nlg-1 generated through its proteolytic cleavage can bind to presynaptic metabotropic glutamate receptors, ultimately leading to their activation and the suppression of glutamate release, thereby reducing synaptic strength [ 57 ]. Likewise, the induction of Nlg-3 proteolytic cleavage by protein kinase C results in reduced synaptic strength that can be counteracted by the prevention of cleavage.…”
Section: The Neurexin–neuroligin Mediated Trans-synaptic Modulationmentioning
confidence: 99%
“…Notably, the authors showed that MMP-9-dependent shedding of NLGN1 leads to the destabilization of presynaptic NRX1β and downregulation of synaptic transmission. Recent data suggest that the soluble extracellular domain of NLGN1 binds to metabotropic glutamate receptor 2 (mGluR2), and thereby decreases synaptic strength [ 89 ].…”
Section: Regulation Of Mmp-9 Substrates By Small Rho Gtpasesmentioning
confidence: 99%